Partisipasi Masyarakat dalam Kebijakan Publik: Memperkuat Demokrasi dan Meningkatkan Kepercayaan Masyarakat terhadap Pemerintah - Wahyuni, Sri; Sudirman, Rahmawati (MAN 4 Kota Pekanbaru, 2026)
Public participation in public policy is a fundamental element in democratic governance, yet its implementation in Indonesia often remains procedural and has limited influence on policy outcomes. Strengthening meaningful participation is therefore essential to ensure that public policy reflects the interests and needs of society. This research aims to analyze community participation in public policy by examining its role in supporting democratic and inclusive governance. This article employs a literature review method by analyzing data from books, academic publications, and relevant reports discussing public participation in policy processes. The results indicate that increasing meaningful participation in policy formulation and implementation can improve government accountability and ensure that public policies better represent the interests of the broader community.